Tracing the consequences of child poverty - Boyden, Jo (Policy Press, 2019)
Available Open Access under CC-BY-NC licence. Using life course analysis from the Young Lives study of 12,000 children growing up in Ethiopia, India, Peru and Vietnam over the past 15 years, this book draws on evidence on two cohorts of children, aged from 1 to 15 and from 8 to 22. It examines how poverty affects children's development in low and middle income countries, and how policy has been used to improve their lives, then goes on to show when key developmental differences occur. It uses new evidence to develop a framework of what matters most and when and outlines effective policy approaches to inform the no-one left behind Sustainable Development Goal agenda.